The burden of injury in Central, Eastern, and Western European sub-region: a systematic analysis from the Global Burden of Disease 2019 study - Haagsma, Juanita; Charalampous, Periklis; Ariani, Filippo; Gallay, Anne; Moesgaard Iburg, Kim; Nena, Evangelia; Ngwa, Che Henry; Rommel, Alexander; Zelviene, Ausra; Abegaz, Kedir Hussein; Al Hamad, Hanadi; Albano, Luciana; et al. (Archives of public health, 2022)
Injury remains a major concern to public health in the European region. Previous iterations of the Global Burden of Disease (GBD) study showed wide variation in injury death and disability adjusted life year (DALY) rates across Europe, indicating injury inequality gaps between sub-regions and countries. The objectives of this study were to: 1) compare GBD 2019 estimates on injury mortality and DALYs across European sub-regions and countries by cause-of-injury category and sex; 2) examine changes in injury DALY rates over a 20 year-period by cause-of-injury category, sub-region and country; and 3) assess inequalities in injury mortality and DALY rates across the countries.
Gesehen am 22.07.2022